The Effect of macroeconomic variables on the growth of guarantee insurance - Hong, Min Young (KDI School, 2011)
As world economy has shown dynamic reaction to the changes of market leading indicator including exchange rate changes, stock price, current account and GDP, economic growth also has given impact on numerous industries directly as well as indirectly. In recent years, a number of researchers conducted studies on the relationship between the growth of economy and financial sector. However, the research on the insurance industry development has been done infrequently even if insurance is one of the important sectors of the financial industry. This paper covers how much impact of economic indicators is given to the development of surety and credit insurance in Korea, one of the non-life insurance classes. According to the monthly premium income and the economic factors during the first decade of this century, each economic indicator has different effects to the development of each surety and credit insurance product, as well as, total premium income. This article uses ADF tests, Granger causality test and cointegration test, and introduces the impulse response analysis to observe responses of surety and credit insurance industry to economic shocks.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: ADF test.